2023
DOI: 10.1097/md.0000000000034015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of postoperative radiotherapy on the survival of patients with stage III non-small cell lung cancer: A CONSORT-compliant analysis using the SEER database

Abstract: Background: Postoperative radiotherapy (PORT) is commonly used to treat patients with resected stage III non-small cell lung cancer (NSCLC), but its effectiveness remains uncertain. This retrospective cohort study aimed to investigate the impact of PORT on overall survival (OS) and evaluate its heterogeneity among subgroups of patients.Methods: A total of 6305 patients with resected stage III NSCLC were included in this study from the Surveillance, Epidemiology, and End Results (SEER) database. Propensity scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…While the prognostic value of PLNs and the PD ratio has been well-recognized and verified in pN2 NSCLC patients receiving PORT [21], controversy exists regarding the use of lymph node burden as a predictive factor for PORT. In serial analyses based on the Surveillance, Epidemiology, and End Results (SEER) database, Wu et al included all resected stage III NSCLC patients and reported a significant OS improvement with PORT in the stage IIIA/pN2 and PD ratio > 1/3 subgroups [22]. Urban et al and Wang et al, focusing on resected pN1-2 and pN2-stage IIIA NSCLC, suggested a more profound PORT survival benefit with a PD ratio >50% or PLNs > 3, respectively [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…While the prognostic value of PLNs and the PD ratio has been well-recognized and verified in pN2 NSCLC patients receiving PORT [21], controversy exists regarding the use of lymph node burden as a predictive factor for PORT. In serial analyses based on the Surveillance, Epidemiology, and End Results (SEER) database, Wu et al included all resected stage III NSCLC patients and reported a significant OS improvement with PORT in the stage IIIA/pN2 and PD ratio > 1/3 subgroups [22]. Urban et al and Wang et al, focusing on resected pN1-2 and pN2-stage IIIA NSCLC, suggested a more profound PORT survival benefit with a PD ratio >50% or PLNs > 3, respectively [23,24].…”
Section: Discussionmentioning
confidence: 99%